An Exploration of Overconfidence and the Disposition Effect in the Stock Market - Benomar Ikram; Ben El Haj Fouad; Chelh Sara (International Journal of Financial Studies, 2023)
This paper offers a comprehensive empirical overview of the impact of overconfidence in the stock market, thus contributing to the existing research literature on this topic. The study employs a bibliometric approach that utilizes the VOSviewer to extract and analyze 277 articles registered between 1992 and January 2023. By providing a detailed analysis of the literature, this research expands our understanding of the impact of overconfidence in the stock market and offers avenues for future studies in this area. The results of this analysis are noteworthy, as they reveal several important findings. These include the exponential growth of scientific production in recent decades, the concentration of research in specific journals indexed in the Journal Citation Reports, the presence of institutional co-author networks, and the thematic and temporal segregation of financial behavior concepts. The most significant finding of this study is the identification of six major clusters: investor behavior during times of crisis; behavioral finance; herding and risk-taking concepts; psychological and cognitive decisions; emotions and decision-making; and the performance of stocks. This temporal evolution of research demonstrates the emergence of various perspectives on the relationship between individual financial behavior and the global market. This study represents a pioneering effort in the field of bibliometric analysis as it is the first to specifically examine the subject of overconfidence in the stock market using this method.